Analysis of Teacher Strategies in Integrating Technology in Islamic Religious Education Learning in Elementary Schools: Analisis Strategi Guru dalam Mengintegrasikan Teknologi pada Pembelajaran Pendidikan Agama Islam di Sekolah Dasar - Nurdin, Jajang Ahmad; Wahyudin, Wahyudin; Dimyati, Endang; Nurjamin, Asep; Rahayu, Ayu Puji; Jalaludin, Dodi Misbah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The rapid development of information and communication technology has transformed educational practices, requiring more interactive and student-centered learning environments. Specific Background In Islamic Religious Education at the elementary level, conventional teaching approaches remain dominant, while digital tools offer opportunities for more engaging instruction. Knowledge Gap However, studies examining comprehensive teacher strategies in integrating technology, including innovation, challenges, and solutions, remain limited. Aims This study aims to analyze teacher strategies in integrating technology, identify instructional innovations, examine implementation challenges, and explore solutions in Islamic Religious Education learning. Results The findings indicate that teachers utilized instructional videos, interactive quizzes through platforms such as Wordwall and Quizizz, and web-based learning via Google Sites. These practices increased student engagement, participation, and understanding, as reflected in improved average scores from pre-test to post-test. Nevertheless, constraints such as limited technological infrastructure, unstable internet access, and insufficient digital literacy were identified. Teachers addressed these issues through personal device utilization, institutional collaboration, and continuous learning efforts. Novelty This study provides a comprehensive perspective by integrating analysis of teacher strategies, innovations, constraints, and solutions within a single framework. Implications The results suggest that technology integration can support improved learning processes in Islamic education when accompanied by adequate resources, institutional support, and enhanced teacher digital competence. Highlights • Increased student engagement observed during technology-supported instruction• Higher post-test scores indicate improved conceptual understanding• Implementation constrained by infrastructure and digital literacy limitations Keywords Technology Integration; Teacher Strategy; Islamic Education; Learning Outcomes; Digital Learning